Neonatal Septic Shock and Hemodynamic Monitoring in Preterm Neonates in an NICU: Added Value of Electrical Cardiometry in Real-Time Tailoring of Management and Therapeutic Strategies - Gatelli, Italo F.; Vitelli, Ottavio; Fossati, Marco; De Rienzo, Francesca; Chiesa, Gaia; Martinelli, Stefano (American Journal of Perinatology, 2021)
Objective Electrical cardiometry is an impedance-based monitoring technique that provides data on several hemodynamic parameters in a noninvasive way. There is limited information on clinical utility of the application of this technique in neonates.Study Design In this study, we describe the case of a preterm neonate born at 302/7 weeks of gestational age who developed severe systemic infection with fluid refractory septic shock on day 2 of life.Discussion Electrical cardiometry was used and proved very helpful in real-time guiding the choice and the dosing of the most appropriate inotrope drugs in this patient. In addition, it promptly underlined an abrupt drop of systemic vascular resistances occurring after administration of the first dose of antibiotic, thus warning the attending neonatologist to institute appropriate treatment before the clinical conditions could further worsen.Conclusion This case report suggests that electrical cardiometry could be a useful tool in assessing, monitoring, and guiding care of neonates who develop severe septic shock. We suggest that electrical cardiometry is a promising approach in the management strategies of such patients that warrants informative clinical trials.Key Points
Keywords: electrical cardiometry; septic shock; newborn; hemodynamic monitoring; thoracic electrical bioimpedance; cardiac output